Caso clínico: Retraso del lenguaje - Bielsa, A; Sibel, A.; Tomás, J. (Revista de Psiquiatría Infanto-Juvenil, 1999)
Adrián’s parents from 3 a. 4 m. of age, they asked us for a consultation in our service in January 98, for presenting an alteration in communication and language delay with comprehension difficulties; associated with seemingly unstable attitude and attention. They describe him as a moved, restless, oppositional and stubborn child, so perhaps he has a low tolerance for frustration. The described picture is accompanied, according to the parents, also with mood changes.